The Role of Job Satisfaction in Mediating Work Motivation, Compensation and Organizational Culture on Employee Performance - Norawati, Suarni; Nugraha, Saptian Dana; Jatiningrum, Citrawati (Universitas Pamulang, 2024)
The hotel industry is experiencing intense competition to attract customers who will take advantage of the hotel's services. Therefore, company demands for employee performance are increasingly higher, and several factors can affect employee performance. This research examines the effect of motivation, compensation, and organizational culture on performance through job satisfaction. The research sample consisted of 87 employee hotels. Data analysis and hypothesis testing were performed using the Smart PLS program's structural equation modeling (SEM) and data processing. The findings demonstrate a significant impact of motivation, compensation, and organizational culture on job satisfaction rather than employee performance. It has been demonstrated that motivation, compensation, and organizational culture indirectly influence performance through job satisfaction.